Effectiveness of the Mayor's Regulation on Electronic-Based Service Innovation in Batu City : Batu Smart City Case Study - Adhitama, Muhammad Okto; Wardiyanto, Bintoro; Setijaningrum, Erna (REFORMASI, 2025)
Developed countries are seen from the use of technology as one of the indicators. The challenges of the Industrial Revolution 4.0 and Civil Society 5.0 make Regional Governments feel compelled to create an integrated Smart City with the term Smart City. Smart City is an innovation that is permitted by local governments. The legal basis in the form of a Presidential Instruction and several derivative policies with a target of 100 Smart Cities continues to be implemented. Batu City, as one of the Smart City targets, is experiencing dynamics in its implementation. This can be seen from the average level of increase and also changes in regulations which were originally regulated in Mayor Regulation Number 78 of 2017, revised to Mayor Regulation Number 3 of 2021. Therefore, researchers took the aspect of legal effectiveness to be able to analyze these dynamics. The research method uses juridical-empirical with descriptive analysis. The data taken is in the form of interviews and official documents regarding the implementation of Batu Smart City regulations. The result is that legal effectiveness in Batu Smart City has been effective since the policy update by collaborating with elements outside the government. The influencing factor is social adaptation which always requires time and socialization support from the Batu City Government on all electronic government featuresNegara maju dilihat dari pemanfaatan teknologi sebagai salah satu indikatornya. Tantangan Revolusi Industri 4.0 dan Civil Society 5.0 membuat Pemerintah Daerah merasa dituntut untuk mewujudkan Smart City yang terpadu dengan istilah Smart City. Smart City merupakan suatu inovasi yang dicanangkan oleh pemerintah daerah. Landasan hukum berupa Instruksi Presiden dan beberapa kebijakan turunan dengan target 100 Smart City terus dilaksanakan. Kota Batu sebagai salah satu sasaran Smart City mengalami dinamika dalam penyelenggaraannya. Hal ini terlihat dari rata-rata tingkat kenaikan dan juga perubahan regulasi yang semula diatur dalam Peraturan Wali Kota Batu Nomor 78 Tahun 2017 direvisi menjadi Peraturan Wali Kota Batu Nomor 3 Tahun 2021. Oleh karena itu, peneliti mengambil aspek efektivitas hukum untuk dapat menganalisis dinamika tersebut. Metode penelitian menggunakan yuridis-empiris dengan analisis deskriptif. Data yang diambil berupa wawancara dan dokumen resmi terkait implementasi regulasi Batu Smart City. Hasilnya adalah efektivitas hukum di Batu Smart City sudah efektif sejak pembaruan kebijakan dengan berkolaborasi dengan elemen di luar pemerintahan. Faktor yang mempengaruhi adalah adaptasi sosial yang selalu membutuhkan waktu dan dukungan sosialisasi dari Pemerintah Kota Batu pada semua fitur pemerintahan elektronik.